2005
DOI: 10.5395/jkacd.2005.30.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofEnterococcus faecalissonicated extracts on IL-2, IL-4 and TGF-β1 production from human lymphocytes

Abstract: In order to examine the immunoresponse of host cells to Enterococcus faecalis, this in vitro study monitored the production of Interleukin-2 (IL-2), Interleukin-4 (IL-4) and Transforming growth factor-β 1 (TGF-β 1) in human lymphocytes. Lymphocytes were activated with PHA in the presence or abscence of sonicated extracts of E. Faecalis (SEF) and further incubated for 72 hours. The level of each cytokine was measured by ELISA. Data were analyzed with Kruskal-Wallis test and MannWhitney U test (P < 0.05). PHA-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“… 16 , 17 Kim et al suggested the ability of the E. faecalis to suppress IL-2 and IL-4 production by lymphocytes to be one of the factors. 18 C. albicans is usually associated with bacteria, especially E. faecalis . 19 The selection of these pathogens as test organisms was because of their clinical importance and extensive use in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 Kim et al suggested the ability of the E. faecalis to suppress IL-2 and IL-4 production by lymphocytes to be one of the factors. 18 C. albicans is usually associated with bacteria, especially E. faecalis . 19 The selection of these pathogens as test organisms was because of their clinical importance and extensive use in previous studies.…”
Section: Discussionmentioning
confidence: 99%